Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Use implicit differentiation to find the equations of the tangent and normal lines at the point (3, 1) for the curve (y2 + 4)y = 13.

Use Implicit Differentiation To Find The Equations Of The Tangent And Normal Lines At The Point 3 1 For The Curve Y2 4y 13 class=

Sagot :

Given the equation below;

[tex](x^2+4)y=13[/tex]

To find the derivative of the equation above, we will defferentiate implicitly, this is shown below

[tex]\begin{gathered} (x^2+4)y=13 \\ \text{ Remove bracket} \\ x^2(y)+4(y)=13 \\ x^2y+4y=13 \end{gathered}[/tex][tex]\begin{gathered} 2xy+x^2\frac{\mathrm{d}y}{dx}+4\frac{\mathrm{d}y}{dx}=0 \\ x^2\frac{\mathrm{d}y}{dx}+4\frac{\mathrm{d}y}{dx}=-2xy \\ \text{factor }\frac{\mathrm{d}y}{dx} \\ \frac{\mathrm{d}y}{dx}(x^2+4)=-2xy \end{gathered}[/tex][tex]\frac{\mathrm{d}y}{dx}=\frac{-2xy}{(x^2+4)}[/tex]

At point (3, 1) we can obtain the value of the slope ( dy/dx), by substituting for x and y.

[tex]\begin{gathered} x=3,y=1 \\ \frac{\mathrm{d}y}{dx}=\frac{-2xy}{(x^2+4)} \\ \frac{\mathrm{d}y}{dx}=\frac{-2(3)(1)}{3^2+4}=\frac{-6}{9+4}=-\frac{6}{13} \end{gathered}[/tex]

Using the point-slope equation of a line formula as shown below

[tex]y-y_1=m(x-x_1)[/tex]

We can use the above to find the tangent to the line equation. then we have:

[tex]\begin{gathered} y-1=-\frac{6}{13}(x-3) \\ y-1=-\frac{6}{13}x+\frac{18}{13} \\ y=-\frac{6}{13}x+\frac{18}{13}+1 \\ y=-\frac{6}{13}x+\frac{31}{13} \end{gathered}[/tex]

To find the normal line equation, we have to use the condition for perpendicularity of two lines, that is

[tex]\begin{gathered} m_1=-\frac{1}{m_2} \\ If_{} \\ m_1\Rightarrow\text{slope of the tangent line} \\ m_2\Rightarrow\text{slope of the normal line} \\ m_2=-\frac{1}{m_1} \\ \text{Thus, the slope of the normal line is} \\ =\frac{13}{6} \end{gathered}[/tex]

Using point-slope equation of a line we can also find the normal line equation.

[tex]\begin{gathered} y-1=\frac{13}{6}(x-3) \\ y-1=\frac{13}{6}x-\frac{13}{2} \\ y=\frac{13}{6}x-\frac{13}{2}+1 \\ y=\frac{13}{6}x-\frac{11}{2} \end{gathered}[/tex]

Hence, the tangent line and normal line equation are

[tex]\begin{gathered} \text{tangent line}\Rightarrow y=-\frac{6}{13}x+\frac{31}{13}\text{ } \\ \text{normal line}\Rightarrow y=\frac{13}{6}x-\frac{11}{2} \end{gathered}[/tex]

This can be simplified as;

[tex]\begin{gathered} \text{tangent line}\Rightarrow y=-\frac{6}{13}x+2\frac{5}{13}\text{ } \\ \text{normal line}\Rightarrow y=2\frac{1}{6}x-5\frac{1}{2} \end{gathered}[/tex]

Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.